2011 IEEE 17th International Conference on Embedded and Real-Time Computing Systems and Applications 2011
DOI: 10.1109/rtcsa.2011.57
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Preemptions and Migrations in Real-Time Multiprocessor Scheduling Algorithms by Releasing the Fairness

Abstract: Over the past two decades, numerous optimal scheduling algorithms for real-time systems on multiprocessor platforms have been proposed for the Liu & Layland task model. However, recent studies showed that even if optimal algorithms can theoretically schedule any feasible task set, suboptimal algorithms usually perform better when executed on real computation platforms. This can be explained by the runtime overheads that such optimal algorithms induce.We have observed that all current optimal online multiproces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…That is, PFair algorithms cause much more overheads than Boundary Fair (or DPFair) approaches which in turn are more costly in terms of preemptions than EKG. Finally, it was shown that RUN and U-EDF dominate all these algorithms [1], [15].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…That is, PFair algorithms cause much more overheads than Boundary Fair (or DPFair) approaches which in turn are more costly in terms of preemptions than EKG. Finally, it was shown that RUN and U-EDF dominate all these algorithms [1], [15].…”
Section: Related Workmentioning
confidence: 99%
“…Finally, a previous version of the U-EDF algorithm was presented in [1] showing a drastic improvement of the number of preemptions and migrations due to the fairness release. An interesting observation issued from the study of all the aforementioned algorithms, is the fact that the number of preemptions and migrations decreases as the fairness constraint is relaxed.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The scheduling algorithm decides which processor the task will be executed on, as well as the order of the tasks' execution. Although a scheduling algorithm may be optimal, sometimes it cannot be applied practically [9]. This is because of the scheduling overheads, in terms of task preemptions and migrations that accompany its work.…”
Section: Introductionmentioning
confidence: 99%